-2(x-7)=7x-2(x+1)+24

Simple and best practice solution for -2(x-7)=7x-2(x+1)+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-7)=7x-2(x+1)+24 equation:


Simplifying
-2(x + -7) = 7x + -2(x + 1) + 24

Reorder the terms:
-2(-7 + x) = 7x + -2(x + 1) + 24
(-7 * -2 + x * -2) = 7x + -2(x + 1) + 24
(14 + -2x) = 7x + -2(x + 1) + 24

Reorder the terms:
14 + -2x = 7x + -2(1 + x) + 24
14 + -2x = 7x + (1 * -2 + x * -2) + 24
14 + -2x = 7x + (-2 + -2x) + 24

Reorder the terms:
14 + -2x = -2 + 24 + 7x + -2x

Combine like terms: -2 + 24 = 22
14 + -2x = 22 + 7x + -2x

Combine like terms: 7x + -2x = 5x
14 + -2x = 22 + 5x

Solving
14 + -2x = 22 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
14 + -2x + -5x = 22 + 5x + -5x

Combine like terms: -2x + -5x = -7x
14 + -7x = 22 + 5x + -5x

Combine like terms: 5x + -5x = 0
14 + -7x = 22 + 0
14 + -7x = 22

Add '-14' to each side of the equation.
14 + -14 + -7x = 22 + -14

Combine like terms: 14 + -14 = 0
0 + -7x = 22 + -14
-7x = 22 + -14

Combine like terms: 22 + -14 = 8
-7x = 8

Divide each side by '-7'.
x = -1.142857143

Simplifying
x = -1.142857143

See similar equations:

| x+(x+1)=218 | | 4n*3=144 | | X(70-20+10)=0 | | n=96/4 | | X=12y-4 | | 3a^2+5a-28= | | 4y+12=5x+14 | | 56x^3-72x^2+35x-45= | | 3a^2+6a-28= | | h=18+-3t | | n-15=78 | | (12-3x)=0 | | 50/0.5=n | | (5x+7)(12-3x)=0 | | n-1=23 | | n*2=3.5 | | 2y+bx=5 | | (8-X0/10.5=0.75 | | n=342*0 | | 34*n=34 | | u^2-13u-21=0 | | 0.44(y-200)+0.02y=0.12+0.07(200) | | (1/3)= | | (7x-3)(-2)+x=0 | | 3-12+7=10+x-3 | | 3x(2x-4)-1=-1 | | x+y=325 | | -9.6+x=-13.5 | | 22-7m= | | 5(x-2)=5-2x | | x-5.5=8.6 | | 21a^5+211a^3b^2+10ab^4=0 |

Equations solver categories